Effects of Remifentanil Gradual Withdrawal Combined with Postoperative Infusion on Postoperative Hyperalgesia in Patients Undergoing Laparoscopic hysterectomy: A Factorial Design, Double-Blind, Randomized Controlled Trial - Luo M; Han X; Li H; Zhou G; Chen H; Gao F (Dove Medical Press, 2024)
Meng Luo,1,2,* Xue Han,1,2,* Huan Li,1,2 Guangyue Zhou,1,2 Haoxuan Chen,1,2 Fang Gao1,2 1Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 2Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Fang Gao, Department of Anesthesiology, the Affiliated Hospital of Xuzhou Medical University, No. 99 Huaihai West Road, Xuzhou, Jiangsu, 221002, People's Republic of China, Tel +86-18052268331, Email gaofangxz@126.comBackground: Remifentanil-induced hyperalgesia (RIH) increases the risk of persistent postoperative pain, making early postoperative analgesic therapy ineffective and affecting postoperative patient satisfaction. This study aimed to verify the effects of gradual withdrawal of remifentanil combined with postoperative pump infusion of remifentanil on postoperative hyperalgesia and pain in patients undergoing laparoscopic hysterectomy.Methods: This trial was a factorial design, double-blind, randomized controlled trial. Patients undergoing laparoscopic hysterectomy were randomly allocated to the control group, postoperative pump infusion of remifentanil group, gradual withdrawal of remifentanil group, or gradual withdrawal plus postoperative pump infusion of remifentanil group (n = 35 each). The primary outcome was postoperative mechanical pain thresholds in the medial forearm. The secondary outcomes included postoperative mechanical pain thresholds around the incision, pain numeric rating scale scores, analgesic utilization, awakening agitation or sedation scores, a 15-item quality of recovery survey, and postoperative complications.Results: Gradual withdrawal of remifentanil significantly increased postoperative pain thresholds versus abrupt discontinuation (P < 0.05), whereas postoperative infusion did not show significant differences compared to the absence of infusion (P > 0.05). The combined gradual withdrawal and postoperative infusion group exhibited the highest thresholds and had the lowest postoperative pain scores and analgesic requirements as well as the highest quality of recovery scores (P < 0.05). No significant differences were observed for agitation scores, sedation scores, or complication rates (P > 0.05).Conclusion: The novel combined gradual withdrawal and postoperative infusion of remifentanil uniquely attenuates postoperative hyperalgesia, pain severity, analgesic necessity, and improves recovery quality after laparoscopic hysterectomy.Keywords: opioid-induced hyperalgesia, remifentanil-induced hyperalgesia, laparoscopic hysterectomy, mechanical pain thresholds, postoperative recovery